2014
DOI: 10.1007/jhep04(2014)075
|View full text |Cite
|
Sign up to set email alerts
|

Reggeon field theory for large Pomeron loops

Abstract: Abstract:We analyze the range of applicability of the high energy Reggeon Field Theory H RFT derived in [1]. We show that this theory is valid as long as at any intermediate value of rapidity η throughout the evolution at least one of the colliding objects is dilute. Importantly, at some values of η the dilute object could be the projectile, while at others it could be the target, so that H RFT does not reduce to either H JIM W LK or H KLW M IJ . When both objects are dense, corrections to the evolution not ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 89 publications
0
41
0
Order By: Relevance
“…The prime example is the operator representing the Reggeized gluon, which played a very important role in the development of high energy evolution ideas, especially in the perturbative domain. Another example of an interesting nonsinglet observable, is inclusive gluon production amplitude, which is invariant only under the vector subgroup of SU L (N c ) × SU R (N c ) [35]. Recently ref.…”
Section: Jhep08(2014)114mentioning
confidence: 99%
See 1 more Smart Citation
“…The prime example is the operator representing the Reggeized gluon, which played a very important role in the development of high energy evolution ideas, especially in the perturbative domain. Another example of an interesting nonsinglet observable, is inclusive gluon production amplitude, which is invariant only under the vector subgroup of SU L (N c ) × SU R (N c ) [35]. Recently ref.…”
Section: Jhep08(2014)114mentioning
confidence: 99%
“…However some interesting observables, like single gluon inclusive production require the knowledge of observables which are singlets only under the vector subgroup of SU L (N c )×SU R (N c ) [35]. It is thus useful to generalize the Hamiltonian so that it generates correct evolution of such operators.…”
Section: Jhep08(2014)114mentioning
confidence: 99%
“…In building our model we rely on the BFKL Pomeron calculus, since the relation to diffractive physics is more evident in this approach. However, we are aware that the CGC/saturation approach gives a more general pattern [101][102][103][104]. In Refs.…”
Section: Theoretical Input and 'Dressed' Pomeron Green Functionmentioning
confidence: 99%
“…In addition in Refs. [103,104] it is shown that for such Y , we can safely use the Mueller-Patel-Salam-Iancu (MPSI) approach [106][107][108][109], which allows us to calculate the contribution to the resulting BFKL Pomeron Green function (see Fig. 14a):…”
Section: Theoretical Input and 'Dressed' Pomeron Green Functionmentioning
confidence: 99%
“…The BFKL Pomeron calculus turns out to be close to the old Reggeon theory [80], so, for calculating the inclusive characteristics of multiparticle production, we can apply the Mueller diagram technique [81]. The relation between these two approaches has not yet been established, but they are equivalent [74][75][76][77] where BFKL denotes the intercept of the BFKL Pomeron.…”
Section: Introductionmentioning
confidence: 99%